Effect of Deep Relaxation Technique on Cardiac Autonomic Dysfunction in Type 2 Diabetes Mellitus - Rahman, Farhana; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2018)
Background: Type 2 Diabetes Mellitus (T2DM) may be associated with autonomic dysfunction. Performance of deep relaxation technique (DRT) may cause upturn of this deranged nerve function. Objective: To evaluate the impact of DRT on cardiac autonomic nerve function by analysis of time domain series of Heart Rate Variability (HRV) in T2DM patients. Methods: This prospective study was carried out on 30 female T2DM patients aged 50-55 years with duration of diabetes of 5-10 years enrolled from the Out Patient Department of Endocrinology, Bangabandhu Sheikh Mujib Medical University, Dhaka. They performed DRT (20 minutes twice daily) for 3 months. Thirty apparently healthy female with similar age who did not perform DRT or any other form of exercise, were included as control. To assess the cardiac autonomic nerve function, time domain measures of HRV of all subjects were recorded by a data acquisition device Power Lab (Australia). HRV data of all subjects were collected at baseline (pre) and also after 3 months(Post). For statistical analysis, paired and independent sample t-test were used. Results: The pre-intervention values of resting HR was significantly higher (p<0.001) and mean R-R interval, SDRR, CVRR, SDSD, RMSSD and pRR50% were significantly lower (p<0.001) in all diabetic patients compared to control. After 3 months of DRT, there was significant decrement in resting mean heart rate (p<0.01) and significant increment in mean R-R interval, SDRR, CVRR, SDSD, RMSSD and pRR50% (p<0.001) compared to their pre-intervention values. Conclusion: Cardiac autonomic nerve dysfunction may occur in T2DM and 3 months regular practice of DRT mayy significantly improv cardiac autonomic nerve function with parasympathetic dominance. J Bangladesh Soc Physiol. 2018, June; 13(1): 22-28